Dietrich Bonhoeffer and the Evangelical Moment in American Public Life - Gushee, David P. (Studies in Christian-Jewish Relations, 2011)
This essay was delivered during a panel discussion entitled "'Costly Discipleship and Contemporary Culture: Bonhoeffer as a Model for Religious Activism" during the conference Dietrich Bonhoeffer for Our Times: Jewish and Christian Perspectives, cosponsored by the Center for Christian-Jewish Learning at Boston College, the United States Holocaust Memorial Museum, Hebrew College, and Andover-Newton Theological School, September 18, 2006. The author argues that conservative American evangelicals "often conflate loyalty to Jesus Christ with loyalty to the United States of America. They weave together loyalty to Jesus Christ with loyalty to the president, the party, the troops, the flag, or the nation." For the author, the witness of Dietrich Bonhoeffer encourages a strong resistance to such a confusion of loyalties.